Waterfront, St. Michael - Washington State University Vancouver Library; http://library.vancouver.wsu.edu/
A view along the waterfront at St. Michael. The bay is on the left and the buildings can be seen in the distance. Grasses grow along the shore and a light covering of snow is on the ground. 3.25 x 5.25 in.